Concentrations of Traffic Related Pollutants in the Vicinity of Different Types of Urban Crossroads - Jandacka, Dusan; Durcanska, Daniela; Kovalova, Dasa (Communications - Scientific letters of the University of Zilina, 2019)
Pollution of the air by gases and particulate matter is a problem of everyday life. Particulate matter (PM) is one of the hazardous pollutants causing deterioration of the environment and thus quality of life of the population. Long-term exposure to effects of increased concentrations of gaseous pollutants can also cause deterioration of the environment and human health. Particulate matter and gases production by the road transport is a burning issue, particularly for larger urban areas. Many factors influence the air quality what determines its development and changes. Air pollution monitoring was focused on a possible change in the concentrations of pollutants after the change of the crossroad - three-arm crossroad to the roundabout. The subject of this paper is monitoring particulate matter (PM1, PM2.5, PM10) and gases (nitrogen oxides NO, NO2, NOx) in the vicinity of crossroads in the urban area and an evaluation of fraction ratios PM10, PM2.5 and PM1 with regard to construction of crossroad, meteorological conditions and traffic volume. The roundabout has specific construction and routing traffic, what can influence on production and dispersion of traffic related emissions. The obtained results indicate a decrease in particulate matter concentrations at the roundabout over a three-arm crossroad and an increase in nitrogen oxides concentrations at the roundabout compared to the three-arm crossroad. According to the data obtained and analyzed, the PM10 particulate matter concentrations at the roundabout could be reduced by up to 50% over the three-arm crossroad.